Preclinical immunogenicity risk assessment of biotherapeutics using CD4 T cell assays - Walsh, Robin E.; Nix, Angela; Ackaert, Chloé; Mazy, Aurélie; Schockaert, Jana; Pattyn, Sofie; Malherbe, Laurent (Frontiers in Immunology, 2024)
T-cell dependent antibody responses to biotherapeutics remain a challenge to the optimal clinical application of biotherapeutics because of their capacity to impair drug efficacy and their potential to cause safety issues. To minimize this clinical immunogenicity risk, preclinical assays measuring the capacity of biotherapeutics to elicit CD4 T cell response in vitro are commonly used. However, there is considerable variability in assay formats and a general poor understanding of their respective predictive value. In this study, we evaluated the performance of three different CD4 T cell proliferation assays in their capacity to predict clinical immunogenicity: a CD8 T cell depleted peripheral blood mononuclear cells (PBMC) assay and two co-culture-based assays between dendritic cells (DCs) and autologous CD4 T cells with or without restimulation with monocytes. A panel of 10 antibodies with a wide range of clinical immunogenicity was selected. The CD8 T cell depleted PBMC assay predicted the clinical immunogenicity in four of the eight highly immunogenic antibodies included in the panel.Similarly, five antibodies with high clinical immunogenicity triggered a response in the DC:CD4 T cell assay but the responses were of lower magnitude than the ones observed in the PBMC assay.Remarkably, three antibodies with high clinical immunogenicity did not trigger any response in either platform. The addition of a monocyte restimulation step to the DC:CD4 T cell assay did not further improve its predictive value. Overall, these results indicate that there are no CD4 T cell assay formats that can predict the clinical immunogenicity of all biotherapeutics and reinforce the need to combine results from various preclinical assays assessing antigen uptake and presentation to fully mitigate the immunogenicity risk of biotherapeutics.